Is APOE ε4 associated with cognitive performance in early MS?. Issue 4 (July 2020) - Engel, Sinah; Graetz, Christiane; Salmen, Anke; Muthuraman, Muthuraman; Toenges, Gerrit; Ambrosius, Björn; Bayas, Antonios; Berthele, Achim; Heesen, Christoph; Klotz, Luisa; Kümpfel, Tania; Linker, Ralf A.; et al.
Abstract : Objective: To assess the impact of APOE polymorphisms on cognitive performance in patients newly diagnosed with clinically isolated syndrome (CIS) or relapsing-remitting MS (RRMS). Methods: This multicenter cohort study included 552 untreated patients recently diagnosed with CIS or RRMS according to the 2005 revised McDonald criteria. The single nucleotide polymorphisms rs429358 (ε4) and rs7412 (ε2) of the APOE haplotype were assessed by allelic discrimination assays . Cognitive performance was evaluated using the 3-second paced auditory serial addition test and the Multiple Sclerosis Inventory Cognition (MUSIC). Sum scores were calculated to approximate the overall cognitive performance and memory-centered cognitive functions. The impact of the APOE carrier status on cognitive performance was assessed using multiple linear regression models, also including demographic, clinical, MRI, and lifestyle factors. Results: APOE ε4 homozygosity was associated with lower overall cognitive performance, whereas no relevant association was observed for APOE ε4 heterozygosity or APOE ε2 carrier status. Furthermore, higher disability levels, MRI lesion load, and depressive symptoms were associated with lower cognitive performance. Patients consuming alcohol had higher test scores than patients not consuming alcohol. Female sex, lower disability, and alcohol consumption were associated with better performance in the memory-centered subtests of MUSIC, whereas no relevant association was observed for APOE carrier status. Conclusion: Along with parameters of a higher disease burden, APOE ε4 homozygosity was identified as a potential predictor of cognitive performance in this large cohort of patients with CIS and early RRMS.